2019
DOI: 10.1073/pnas.1902091116
|View full text |Cite
|
Sign up to set email alerts
|

TNFR2 promotes Treg-mediated recovery from neuropathic pain across sexes

Abstract: Tumor necrosis factor receptor 2 (TNFR2) is a transmembrane receptor that is linked to immune modulation and tissue regeneration. Here, we show that TNFR2 essentially promotes long-term pain resolution independently of sex. Genetic deletion of TNFR2 resulted in impaired neuronal regeneration and chronic nonresolving pain after chronic constriction injury (CCI). Further, pharmacological activation of TNFR2 using the TNFR2 agonist EHD2-sc-mTNFR2 in mice with chronic neuropathic pain promoted long-lasting pain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 47 publications
6
35
0
Order By: Relevance
“…Peripheral nerve injury models present peripheral inflammation and increased proinflammatory cytokines in spinal and supraspinal structures, such as the PFC ( González-Sepúlveda et al, 2016 ) and amygdala ( Gonçalves et al, 2008 ) as well as with decreased thermal and mechanical nociceptive thresholds and depressive-like behavior. TNF receptor (TNFR) knockout mice are protected against CCI-induced pain; however, inflammation in the hippocampus and depressive-like behavior remain ( Fischer et al, 2019 ). Inflammation of the limbic system also occurs in chronic stress models with increased proinflammatory cytokines in the PFC, hippocampus, raphe nuclei and pituitary ( Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral nerve injury models present peripheral inflammation and increased proinflammatory cytokines in spinal and supraspinal structures, such as the PFC ( González-Sepúlveda et al, 2016 ) and amygdala ( Gonçalves et al, 2008 ) as well as with decreased thermal and mechanical nociceptive thresholds and depressive-like behavior. TNF receptor (TNFR) knockout mice are protected against CCI-induced pain; however, inflammation in the hippocampus and depressive-like behavior remain ( Fischer et al, 2019 ). Inflammation of the limbic system also occurs in chronic stress models with increased proinflammatory cytokines in the PFC, hippocampus, raphe nuclei and pituitary ( Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNFR2 agonist treatment alleviated peripheral and central inflammation and reduced neuronal injury. Importantly, depletion of Tregs abolished the therapeutic effect of TNFR2 agonist treatment (Fischer et al, 2019b), indicating that Treg-TNFR2 mediated responses are essential for the analgesic effect of EHD2-sc-mTNF R2 . Similar, we demonstrated that in EAE mice systemic administration of EHD2-sc-mTNF R2 alleviated inflammation resulting in reduced demyelination and neurodegeneration.…”
Section: Selective Activation Of Tnfr2 Using Agonistic Tnf Muteins Anmentioning
confidence: 96%
“…Summarizing, while studies demonstrate that TNFR1 plays a role for development and maintenance of neuropathic pain, the role of TNFR2 seems to be more restricted to the early phase of pain development, potentially by promoting inflammation through macrophages. Interestingly, we recently demonstrated that TNFR2 −/− mice have chronic non-resolving pain after CCI, a phenotype that is mirrored by depletion of Tregs (Fischer et al, 2019b), suggesting that TNFR2 may also promote analgesic responses via Tregs.…”
Section: Chronic Neuropathic Painmentioning
confidence: 99%
“…Studies in the EAE model demonstrated that exogenous activation of TNFR2 was therapeutic for motor and sensory disease [166]. Indeed, a recent study in a model of peripheral nerve injury confirmed that TNFR2 is therapeutic for neuropathic pain via an immunomodulatory mechanism [167]. Altogether, these data suggest that selective modulation of TNF-TNFR signaling may hold great promise as a new therapeutic intervention to treat MS [168] (Figure 1).…”
mentioning
confidence: 93%